An azobenzene-based heteromeric prodrug for hypoxia-activated chemotherapy by regulating subcellular localization. Issue 57 (2nd July 2018) - Li, Shiying; Jiang, Xueyan; Zheng, Rongrong; Zuo, Shengjia; Zhao, Linping; Fan, Guiling; Fan, Jinghao; Liao, Yonghua; Yu, Xiyong; Cheng, Hong
Abstract : An azobenzene-based heteromeric prodrug (hNDP) was prepared for tumor targeted chemotherapy by regulating subcellular localization. Abstract : An azobenzene-based heteromeric prodrug (hNDP) was prepared for targeted chemotherapy against hypoxic tumor. hNDP could divert the parent drug from nucleus to cytoplasm with lower toxicity, while the azoreduction of hNDP in hypoxia would activate the drug with a robust anti-tumor effect by initiating the apoptosis-related biochemical cascades.